1953
DOI: 10.1021/ja01098a046
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Transformations of Steroids. V. The Oxygenation of 17α-Hydroxyprogesterone to 6β,17α-Dihydroxyprogesterone and 11α,17α-Dihydroxyprogesterone1

Abstract: Incubation of 17a-hydroxyprogesterone with Rhizopus arrhizus Fischer (A.T.C.C. 11145) produced in good yield 6&17adihydroxyprogesterone and in small amounts 1 I ~~~17a-dihydroxyprogesterone. Incubation with Rhizopiis nigricans Ehrh (.4 T C.C R22711) gave excellent yield4 of I 1 ol,17a-dihydrozyprogesterone and very little of 6@,17a-dihydroxyprogesterone DiscussionIn paper 111 of this series? we reported that Rhizopus arrhizus oxygenates desoxycorticosterone in good yield to 6P-hydroxy-1 l-desoxycorticosterone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1954
1954
1970
1970

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Microbiological transformations of steroids are of considerable importance. Much of this work has been carried out by Peterson (306) and his associates, who used partition chromatography routinely in production control (308,212,304,97,98,309,261,126,307,262,310,127,156,263,269,459,285).8…”
Section: B Quantitative Methodsmentioning
confidence: 99%
“…Microbiological transformations of steroids are of considerable importance. Much of this work has been carried out by Peterson (306) and his associates, who used partition chromatography routinely in production control (308,212,304,97,98,309,261,126,307,262,310,127,156,263,269,459,285).8…”
Section: B Quantitative Methodsmentioning
confidence: 99%
“…As has been shown by investigators of the Research Laboratories of the Upjohn Company (14), fermentation of 17a-hydroxyprogesterone by either of the microorganisms Rhizopus nigricans or Rhizopus arrhizus yields lla,17a-dihydroxyprogesterone and a second compound to which the structure of 68, 17a-dihydroxyprogesterone (A4-pregnene-6/3,17 a-diol-3,20-dione) (VIII) had been tentatively assigned. Comparison of the characteristics of the latter biosynthetic product and of its diacetate with those of the synthetic VIII4 and XHI (cf.…”
mentioning
confidence: 93%
“…demonstrated by the Upjohn group that an oxygen function at carbon-11 can be introduced microbiologically by members of the Mucorales (Eppstein et al, 1953a;Eppstein et al, 1953b;Meister et al, 1953aMeister et al, , 1953bMurray and Peterson, 1952;Peterson et al, 1953a;Peterson et al, 1953b), by species of Penicillium (Murray and Peterson, 1953a) and by species of Aspergillus (Murray ). Fried et al (1952) have also demonstrated that Aspergillus niger introduces a hydroxyl with the alpha configuration at carbon-11 of progesterone, 17a-hydroxyprogesterone and 11-desoxy-17-hydroxycorticosterone (Reichstein's substance S).…”
mentioning
confidence: 99%